Identifikasi Secara Serologi Galur Virus Flu Burung Subtipe H5N1 Clade 2.1.3 dan Clade 2.3.2 pada Ayam Petelur (SEROLOGICAL IDENTIFICATION OF AVIAN INFLUENZA STRAIN VIRUS SUBTYPE H5N1 CLADE 2.1.3 AND CLADE 2.3.2 FROM LAYER) - Kusumastuti, Aprilia; ., Syamsidar; Paderi, Agustin Zaharia; Nurhandayani, Arini; Kencana, Gusti Ayu Yuniati (Jurnal Veteriner, 2015)
The aim of the study was to know avian influenza (AI) infection in field by using serology test in threemarketing area of AI vaccines. Haemagglutination inhibition methode was used in this test. There werefour antigen strains of AI subtype H5N1 clade 2.1.3 (AIstrainA/Chicken/West Java/PWT-WIJ/2006, AIstrain A/Chicken/Garut/BBVW-223/2007, AI strain A/Chicken/West Java-Nagrak/30/2007, and AI strainA/Chicken/Pekalongan/BBVW-208/2007) and 2 antigen strains of AI subtype H5N1 clade 2.3.2 (AI strainA/duck/Sukoharjo/BBVW-1428-9/2012 and AI strain A/duck/Sleman/BBVW-1463-10/2012) was used inthis study for HI test. The result presents that 93,33% chicken farms in three marketing area of PT. SanbioLaboratories have positive antibody titre to AI subtype H5N1 clade 2.1.3. This titre may be obtained fromAI clade 2.1.3 vaccination. From 15 samples, 92,86% are positive to AI subtype H5N1 clade 2.3.2A/duck/Sukoharjo/BBVW-1428-9/2012 and 92,31% are positive to A/duck/Sleman/BBVW-1463-10/2012 evenwithout AI clade 2.3.2 vaccination. This antibody titre may be obtained from AI clade 2.1.3 vaccine crossprotection or field infection.
Keywords: Avian influenza, hemaglutination test, clade 2.1.3 of AI H5N1, clade 2.3.2 of AI H5N1